2023
DOI: 10.3233/wor-205194
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sitting time, neck disability and posture in workers using visual display terminals (VDT)

Abstract: BACKGROUND: Musculoskeletal pain represents a major public health problem. Workers who use visual display terminals (VDT) have suffered an increase in neck pain in recent decades. OBJECTIVE: The aim of this study was to analyze the relationship between physical activity (PA), sitting time, posture, and neck disability in a population of employed adults who use a computer at work. METHODS: In this descriptive-correlational study, 88 workers with a mean age of 48.31 years participated. All of the participants fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The level of DBP in the VDT operation group was significantly higher than that in the non-VDT operation group. Garcia-Remeseiro et al [ 63 ] had shown that VDT operation workers tend to cause the incidence of musculoskeletal disorders. Another study showed an association between musculoskeletal disorders and the risk of hypertension [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of DBP in the VDT operation group was significantly higher than that in the non-VDT operation group. Garcia-Remeseiro et al [ 63 ] had shown that VDT operation workers tend to cause the incidence of musculoskeletal disorders. Another study showed an association between musculoskeletal disorders and the risk of hypertension [ 64 ].…”
Section: Discussionmentioning
confidence: 99%